2022
DOI: 10.1177/17562848221102679
|View full text |Cite
|
Sign up to set email alerts
|

Management of hepatorenal syndrome in liver cirrhosis: a recent update

Abstract: Hepatorenal syndrome (HRS) is a serious form of renal dysfunction in patients with cirrhosis and ascites. It is an important component of the acute-on-chronic liver failure (ACLF) syndrome. Significant recent changes in the understanding of the pathophysiology of renal dysfunction in cirrhosis include the role of inflammation in addition to hemodynamic changes. The term acute kidney injury (AKI) is now adopted to include all functional and structural forms of acute renal dysfunction in cirrhosis, with various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 115 publications
(182 reference statements)
0
30
0
1
Order By: Relevance
“…Interestingly, in our study, there were no significant differences in the mortality rates between the three hospital groups among patients who received RRT. The use of RRT is indicated in patients who are unresponsive to pharmacotherapy, develop volume overload or electrolyte derangements, or for those who are not candidates for LTs 34 . Previous studies have reported that patients with HRS who require RRT have a dismal prognosis 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our study, there were no significant differences in the mortality rates between the three hospital groups among patients who received RRT. The use of RRT is indicated in patients who are unresponsive to pharmacotherapy, develop volume overload or electrolyte derangements, or for those who are not candidates for LTs 34 . Previous studies have reported that patients with HRS who require RRT have a dismal prognosis 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Terlipressin has been compared with norepinephrine in several small trials for the management of HRS-AKI, and both are equivalent efficacious [41]. Many hospitals require that norepinephrine to be used in an intensive care unit (ICU) setting, and therefore, the use of norepinephrine is largely dictated by hospital policy rather than drug availability.…”
Section: Practical Tips About Using Terlipressinmentioning
confidence: 99%
“…Colloid solutions containing albumin can treat hypoalbuminemia, hypotension, and acute renal damage. In conjunction with vasopressors, infusion of albumin is also advised for patients with liver cirrhosis who have hepatorenal syndrome (23) .…”
Section: Fluid Administration • Fluid Volume Expansionmentioning
confidence: 99%